Anthropogenic organochlorine compounds as potential tracers for regional water masses: A case study of estuarine plume, coastal eddy, wind-driven upwelling and long-range warm current. (March 2017) - Ya, Miaolei; Wu, Yuling; Li, Yongyu; Wang, Xinhong
Abstract: Water masses are the crucial factor driving the terrigenous anthropogenic organochlorine compounds (OCs) migration from the coast to open sea. Therefore, organochlorine pesticides (OCPs) and polychlorinated biphenyls (PCBs) were investigated in the Northern South China Sea (NSCS), where different types of water masses are generated by the East Asian summer monsoon: Pearl River estuary plume (PREP), Guangdong offshore eddy (GDEC), South China Sea warm current (SCSWC) and wind-driven upwelling current (WDUC). No discrepant distributions of OC concentrations were found in these water masses ( p  > 0.05). However, compositions and diagnostic ratios of HCHs, DDTs, trans - or cis -chlordane and PCBs could reflect the discrepancies in the input, transport and transformation of OCs caused by the hydrological characteristics of water masses, therefore, this allowing them to serve as potential tracers of regional water masses. In detail, α/γ -HCH and β -HCH percentages could indicate the weathered residue in the GDEC, long-range transport in the SCSWC, rapid photodegradation in the surface WDUC and biodegradation in the deep WDUC, respectively. The predominance of o, p' -DDT and p, p' -DDT could indicate fresh input in the PREP, GDEC and WDUC. DDT/DDTs of ratios <0.5 also reflected long-range transport in the SCSWC. Different DDD/DDE ratios indicated different oxygen environments of microbial degradation in the surface and deep water of the WDUC. Trans/cis -chlordane ratios could indicate the selective degradation of trans -chlordane in different water masses. Finally, a higher proportion of penta -PCB could reflect the strong paint additive sources carried by river erosion in the PREP. Graphical abstract: Highlights: Significant differences of OCs existed in the regional water masses. Occurrence of OCs was influenced by the input sources and transport conditions. DDTs, chlordane, especially HCHs were potential indicators of regional water masses.